2013
DOI: 10.1093/pasj/65.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A New Galactic Extinction Map in High Ecliptic Latitudes

Abstract: In this study, we derived a galactic extinction map in high ecliptic latitudes for $ \mid{\beta}\mid$$ >$ 30$ ^\circ$ . The dust temperature distribution was derived from the intensities at 100 and 140 $ \mu$ m with a spatial resolution of 5$ '$ . The intensity at 140 $ \mu$ m was derived from the intensities at 60 and 100 $ \mu$ m of the IRAS data, assuming two tight correlations between the intensities at 60, 100, and 140 $ \mu$ m of the COBE/DIRBE data. We found that these correlations can be separat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although the reddening parameters are derived independently for each spatial pixel, there are clear coherent features in all the derived parameters across the area, on scales larger than the one pixel coherence expected solely from oversampling the 25 pc pixel grid. The distribution of dust extinction shows clear filamentary structure throughout the kiloparsec-scale regions, and is reminiscent of large scale maps within the Milky Way (e.g., Schlegel et al 1998;Froebrich et al 2007;Kohyama et al 2013;Lombardi et al 2011;Schlafly & Finkbeiner 2011;Nidever et al 2012). There is also obvious large scale coherence in the spatial distribution of the reddening fraction f red .…”
Section: The Spatial Distribution Of Derived Reddeningmentioning
confidence: 70%
“…Although the reddening parameters are derived independently for each spatial pixel, there are clear coherent features in all the derived parameters across the area, on scales larger than the one pixel coherence expected solely from oversampling the 25 pc pixel grid. The distribution of dust extinction shows clear filamentary structure throughout the kiloparsec-scale regions, and is reminiscent of large scale maps within the Milky Way (e.g., Schlegel et al 1998;Froebrich et al 2007;Kohyama et al 2013;Lombardi et al 2011;Schlafly & Finkbeiner 2011;Nidever et al 2012). There is also obvious large scale coherence in the spatial distribution of the reddening fraction f red .…”
Section: The Spatial Distribution Of Derived Reddeningmentioning
confidence: 70%
“…mate the reddening (Yasuda et al 2007;Kohyama et al 2013) and because most stars have lower reddening than the calculated limit, the real errors are much lower than that. Several spectra are averaged to produce the stellar spectrum with higher S/N ratio, so any stars with possible peculiar high reddening are averaged out.…”
Section: Dividing By Stellar Spectrummentioning
confidence: 76%
“…Notably, they found that the Local Cavity, the large volume of hot gas around the Sun, is present both in the gas and the dust. However, they also found that the opacity was higher in the dust in the Northern 218 J. Murthy Gontcharov (2012) 2M ASS + Hipparcos photometry Gontcharov (2013) 2M ASS + W ISE photometry Spatial variations of Extinction Law Kohyama et al (2013) total extinction from IRAS emission Sale (2012) Bayesian models M odeling only hemisphere as compared to the Southern, an asymmetry not seen in the gas. This implies that the gas to dust ratio is higher in the Northern hemisphere, a conclusion also drawn by (Knude & Høg 1999).…”
Section: Extinction Mapsmentioning
confidence: 99%